Islamic Economics and Finance as an Alternative for the Current Economic System in the Context of Covid-19 - Doha Rai (Universitas Darussalam Gontor, 2022)
AbstractMost of the economists in the world agreed that there will be a significant difference in the current global economic system in the post of COVID-19 pandemic, even they are waiting for an alternative economic system instead of the current one. Since Islamic Sharia provide us an integrated economic system, detailed by financial instruments and economical solutions, so it seems ready to be the alternative of the current system. The aim of this paper is to discuss the role of Islamic economic as a new strategy in overcoming and manage the problem of the global financial crisis that happened in the post of COVID-19 pandemic. Also, to discuss the effects that have impacted on the world economy during the pandemic period. In order to do that, the paper first presents crises due capitalism and its impacts on the world economy. Then, it analyses the role of Islamic finance for economy during the pandemic and it investigates the indicators of Islamic economic to prove its ability in solving financial crises and to be as an alternative economic system.